Neoplasia Limfoid yang Menyerupai Mesotelioma: Laporan Kasus - Irianto; Puteri, Made Widya Wirayanti; Sunaka, I Wayan; Novitasari (PT Kalbe Farma Tbk., 2025)
Introduction: Lymphoid neoplasms are abnormalities of the hematopoiesis process of the lymphoid line, which can lead to lymphoma or leukemia. Mesothelioma is an abnormal mesothelial cell growth strongly associated with asbestos exposure. In radiology, mesothelioma is usually described as a tissue-dense lesion with well-defined, spiculated borders attached to the thoracic wall. The picture actually only depicts a tissue attached to the thorax, which can be suspected as mesothelioma, but can also be due to other disease processes, such as leukemia, lymphoma, and tuberculosis. Case: A 58-year-old man presented to the emergency room with complaints of shortness of breath. The patient was initially suspected of mesothelioma with suspicion of blood malignancy, but it turned out that the biopsy results were more likely to lead to infiltration of lymphoid neoplasms. Conclusion: In this patient, a lymphatic neoplasm infiltrated the mesothelial tissue and produced a well-demarcated and spiculated tissue picture resembling mesothelioma. Biopsy examination as the gold standard cannot be replaced by radiologic imaging at this time, as many other disease processes can mimic a malignancy.